Household Leverage and the Recession. Issue 5 (20th October 2022) - Jones, Callum; Midrigan, Virgiliu; Philippon, Thomas
Abstract : We evaluate and partially challenge the household leverage view of the Great Recession. In the data, employment and consumption declined more in U.S. states where household debt declined more. We study a model of a monetary union composed of many regions in which liquidity constraints shape the response of employment and consumption to changes in debt. We estimate the model with Bayesian methods combining state and aggregate data. Changes in household credit explain 40% of the differential rise and fall of employment across states, but a small fraction of the aggregate employment decline in 2007–2010. Nevertheless, since household deleveraging was gradual, credit shocks greatly slowed the recovery.